Redefining Defence Expenditures in B9 Countries: A Risk-Based Model for Rational Allocation under Foreign Threat Scenarios - Ondřej Pekař; Vlastimil Šlouf; Martin Blaha; Lenka Brizgalová; Vojtěch Müllner (Obrana a Strategie, 2025)
The article proposes a risk-based model for rational defence expenditure in NATO’s Bucharest Nine (B9) countries that integrates socioeconomic variables and challenges the 2 %-of-GDP benchmark. It contends that optimal funding should reflect both national wealth and the probability and expected consequences of a foreign attack. Applying a quantitative model spanning 2001–2024, with emphasis on the post-2014 environment after Russia’s seizure of Crimea, the authors correlate actual spending with perceived risk and analyse shifts in budgets, threat perceptions, and prosperity, revealing major gaps between observed and rationalised outlays. The results underscore the value of context-sensitive, evidence-grounded budgeting for strategic foresight, credible deterrence, and prudent resource allocation under uncertainty.